Public acceptance of the use of Far-UVC for virus inactivation: Challenges and opportunities - Abbie Ross; Ewan Eadie; Sally H Ibbotson; Paul O'Mahoney (IPEM-Translation, 2023)
Objectives: There is an urgent need for technologies which can reduce the impact of airborne disease transmission. Far-UVC (200–230 nm) is a range of wavelengths growing in relevance for airborne virus disinfection in occupied public spaces. These wavelengths quickly and efficiently inactivate airborne pathogens, while to current knowledge remaining low risk to room occupants. If there is ever to be an effective widespread implementation of these technologies in public spaces, it is important to assess public opinion to ensure appropriate use and understanding of the technology. Methods: A self-administered survey was distributed through social media channels with several questions to gather opinions on using Far-UVC. The survey was distributed between September 2021 and January 2022. Outcome measures included how safe respondents would feel with or without Far-UVC in indoor spaces and how acceptable the technology would be in certain indoor spaces. Results: There were 111 respondents to the survey. The median age range of the respondents was 36–45, most respondents had never studied biology or related science subjects beyond school level (68%, n = 76), and 87% (n = 97) were indoor workers or attended formal education. Less than one-third of respondents had heard of the term ‘Far-UVC’. Though, on learning about the core principles of Far-UVC, respondents became more supportive of its use in public spaces. Acceptance of Far-UVC was strongest in areas where a higher benefit-risk ratio was perceived, such as in hospitals. Conclusion: We have shown that when the basic concepts of Far-UVC are clearly communicated, public opinion on its adoption improves. Without such a general understanding amongst members of the public, Far-UVC may then face challenges in gaining widespread adoption. The assessment of public opinion presented here will help to determine where primary concerns lie, and the actions needed to address these.